1986
DOI: 10.1002/jcp.1041270307
|View full text |Cite
|
Sign up to set email alerts
|

Collagen synthesis by murine bone marrow cell culture

Abstract: Collagen types synthesized by murine bone marrow cells were studied and the effect of lithium chloride on collagen biosynthesis in vitro was investigated. In the liquid culture system used, an adherent, mixed cell population supports hemopoiesis. Radioactive labeling of cell cultures and subsequent fractionation with ammonium sulfate, enzyme digestion, immune precipitation, and gel electrophoresis indicated that the bone marrow cells synthesized precursors to collagen types I, III, and IV, and fibronectin. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Nonetheless, STP-Aii and STP-C488 seem to be organized in a similar fashion in terms of the presence and location of specific structural motifs (Fig. 5) (17), and small collagen-like polypeptides also have stimulating effects on embryonic tissues (18) and bone-marrow stem cell cultures (19). Several proteins including the type 1 macrophage scavenger receptor (20), rat mannose-binding protein (21), human pulmonary surfactant apoprotein (22), and human complement clq subcomplement B chain and C chain (23,24) have also been found to contain collagen-like repeats.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, STP-Aii and STP-C488 seem to be organized in a similar fashion in terms of the presence and location of specific structural motifs (Fig. 5) (17), and small collagen-like polypeptides also have stimulating effects on embryonic tissues (18) and bone-marrow stem cell cultures (19). Several proteins including the type 1 macrophage scavenger receptor (20), rat mannose-binding protein (21), human pulmonary surfactant apoprotein (22), and human complement clq subcomplement B chain and C chain (23,24) have also been found to contain collagen-like repeats.…”
Section: Resultsmentioning
confidence: 99%
“…Among other factors, the interactions of type I and III collagen molecules, as well as the amounts of these collagen molecules relative to one another, may be important for regulation of fibril structure. Waterhouse et al [41] pointed out that lithium does not affect the types of collagen synthesized by murine bone marrow cells, although the relative proportions of collagen types may differ from controls. There is evidence from the work of Adachi et al [78] and Imamura et al [79] that collagen subtypes, V and pNcollagen III, present in the above tissues are considered to have a crucial role in determining the diameter of heterotypic collagen fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen types synthesized by murine bone marrow cells and the effect of lithium chloride on collagen biosynthesis have been studied in vitro experiments [41]. Lithium treatment did not affect the types of collagen synthesized, although the relative proportions of collagen types may differ from controls.…”
Section: Bonementioning
confidence: 99%
“…In arachnoid and dura mater type 1 collagen is in association with type IV collagen [41,42]. Waterhouse et al [37] pointed out that lithium does not affect the types of collagen synthesized by murine bone marrow cells, although the relative proportions of collagen types may differ from controls. Much remains to be investigated about the factors controlling collagen fibril diameter upon lithium treatment and their relationship to the structural disorganization of fibrils caused by lithium.…”
Section: Discussionmentioning
confidence: 97%
“…Smaller proteoglycans are known to play an important interfibrillar role and lithium-induced alterations to these proteoglycans could have a profound effect on the morphology of collagen fibril bundles. Waterhouse et al [37] reported that noncollagenous components in murine bone marrow cell culture media showed changes in response to lithium treatment.…”
Section: Discussionmentioning
confidence: 98%